(Pro)renin Receptor-Dependent Induction of Profibrotic Factors Is Mediated by COX-2/EP4/NOX-4/Smad Pathway in Collecting Duct Cells - Reyes-Martinez, Cristian; Nguyen, Quynh My; Kassan, Modar; Gonzalez, Alexis A. (Frontiers in Pharmacology, 2019)
The binding of prorenin to the (pro)renin receptor (PRR) triggers the activation of MAPK/ERK1/2 pathway, induction of cyclooxygenase-2 (COX-2), NOX-4-dependent production of reactive oxygen species (ROS), and the induction of transforming growth factor β (TGF-β) and profibrotic factors connecting tissue growth factor (CTGF) and plasminogen activator inhibitor (PAI-I) in collecting duct (CD) cells. However, the role of COX-2 and the intracellular pathways involved are not clear. We hypothesized that the PRR activation increases profibrotic factors through COX-2-mediated PGE2 activation of E prostanoid receptor 4 (EP4), upregulation of NOX-4/ROS production, and activation of Smad pathway in mouse CD cells. Recombinant prorenin increased ROS production and protein levels of CTGF, PAI-I, and TGF-β in M-1 CD cell line. Inhibition of MAPK, NOX-4, and COX-2 prevented this effect. Inhibition of MEK, COX-2, and EP4 also prevented the upregulation of NOX-4. Because TGF-β activates Smad pathway, we evaluate the phosphorylation of Smad2 and 3. COX-2 inhibition or EP4 antagonism significantly prevented phosphorylation of Smad 2/3. Mice that were infused with recombinant prorenin showed an induction in the expression of CTGF, PAI-I, TGF-β, fibronectin, and collagen I in isolated collecting ducts as well as the expression of alpha smooth muscle actin (α-SMA) in renal tissues. COX-2 inhibition prevented this induction. These results indicate that the induction of TGF-β, CTGF, PAI-I, and ROS occurs through PRR-dependent activation of MAPK and NOX-4; however, this mechanism depends on COX-2-derived PGE2 production and the activation of EP4 and Smad pathway.